Polylactic acid composition capable of being degraded in triggered mode and preparation method thereof
By using perovskite CsPbBr3 modified by porphyrin derivatives as a photon absorption promoter in polylactic acid, the problem of slow photodegradation speed of polylactic acid is solved, faster photodegradation effect and lower environmental requirements are achieved, and the The cost.
Patent Information
- Application Number
- CN202411778520.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The photodegradation rate of polylactic acid is slow, mainly due to its poor photon absorption performance and the harsh environmental conditions of existing microbial degradation, making it difficult to rapidly degrade in the natural environment.
Perovskite CsPbBr3 modified with porphyrin derivatives is used as a photon absorption promoter, and its photodegradation performance is improved through coordination with the polylactic acid composition. Specific methods include esterification or covalent linkage of 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin with CsPbBr3, constructing a metal organic framework MOF, and enhancing amino adhesion stability through silane coupling agent. improves photon absorption performance.
It significantly improves the photodegradation speed and efficiency of polylactic acid, reduces environmental requirements, achieves faster photodegradation effects, and controls costs.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of functional degradable polylactic acid compositions, and more specifically, to a triggerable degradable polylactic acid composition and a preparation method thereof. Background Art
[0002] Since its invention, plastic has rapidly developed into one of the most widely used materials in the world, but most plastics cannot be naturally degraded after being discarded, which has brought great challenges to the ecological environment. Degradable polymer materials are a type of green and environmentally friendly materials that are expected to replace traditional fossil-based plastics. Among them, polylactic acid has good processing performance and biocompatibility, becoming one of the most representative and promising degradable materials.
[0003] Polylactic acid is obtained by dehydration of lactic acid through condensation reaction. Therefore, there are a large number of ester bonds in the molecular chain of polylactic acid, and the ester bonds break and degrade under the influence of various factors. Specifically, the degradation of polylactic acid can be divided into hydrolysis degradation, thermal degradation, photodegradation, enzymatic degradation and microbial degradation. Among them, microbial degradation is currently a more common degradation method, which is usually achieved by composting or soil burial. However, the number of microorganisms that can degrade polylactic acid in the natural environment is very small, so the degradation rate of polylactic acid in natural soil is very slow and has strict requirements on microbial environmental conditions.
[0004] Photodegradation refers to the degradation of polylactic acid caused by long-term exposure to sunlight. Its mechanism is that the ultraviolet rays in the sunlight will be directly absorbed by the polylactic acid to form excited molecules, and the excited molecules will undergo decomposition reactions to generate free radicals. The free radicals will cause the chemical chains on the polylactic acid to break, thereby causing the degradation of the polylactic acid. Therefore, compared with microbial degradation, photodegradation has lower environmental requirements. However, the speed of photodegradation of polylactic acid is still relatively slow. Therefore, there is an urgent need for a triggerable degradation polylactic acid composition with faster photodegradation. Summary of the invention
[0005] In order to improve the defect that conventional polylactic acid has an insufficient photodegradation speed, the present application provides a triggerable degradable polylactic acid composition that is more suitable for biodegradation and a preparation method thereof.
[0006] In the first aspect, the present application provides a triggerable degradable polylactic acid composition, which adopts the following technical solution: A triggerable degradable polylactic acid composition is obtained by mixing polylactic acid and a photon absorption promoter, wherein the photon absorption promoter is a perovskite CsPbBr modified by a porphyrin derivative 3 .
[0007] The slow photodegradation rate of polylactic acid is mainly due to its poor photon absorption performance, while the perovskite CsPbBr 3It has excellent multi-photon absorption performance. Therefore, when polylactic acid is added with perovskite CsPbBr 3 When the perovskite CsPbBr 3 Under the action of , the photodegradation performance of polylactic acid will be significantly improved.
[0008] But the perovskite CsPbBr 3 There is a certain aggregation quenching effect, which leads to relatively poor stability of the absorbed photons, that is, the perovskite CsPbBr 3 The degradation performance of polylactic acid still needs to be improved.
[0009] The structure of porphyrin is composed of four pyrrol subunits connected by four methyl bridges. The existence of the extended π-electron system in porphyrin provides the basis for various nonlinear optical effects, that is, it has strong nonlinear optical absorption properties. Connecting metal atoms in the middle position of porphyrin can further enhance the properties of porphyrin.
[0010] Metal-organic framework (MOF) is a porous ordered microporous crystalline material with a wide wavelength range and considerable nonlinear optical properties. Porphyrin is constructed into a metal-organic framework (MOF) and coated on the perovskite CsPbBr 3 After that, the perovskite CsPbBr as an inorganic component 3 It will be coordinated with the metal organic framework MOF as an organic component to promote the perovskite CsPbBr 3 The stability of the luminescent molecules and the nonlinear optical capabilities will be significantly improved, thereby obtaining a better multi-photon absorption effect.
[0011] Preferably, the mass ratio of the polylactic acid to the photon absorption enhancer is (85-95): (5-15).
[0012] When the polylactic acid and the photon absorption promoter are in the above mass ratio, the prepared polylactic acid composition will have both better photodegradation effect and cost control.
[0013] Preferably, the porphyrin derivative modified perovskite CsPbBr 3 The preparation method is as follows: firstly, CsPbBr 3 Connected with 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) to obtain CsPbBr 3 -TCPP; then CsPbBr 3 The porphyrin molecules on TCPP act as active growth sites to directly grow the porphyrin-based metal framework, ultimately obtaining the porphyrin derivative-modified perovskite CsPbBr 3 .
[0014] Preferably, the CsPbBr3 It was obtained by connecting with 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) through esterification reaction; The CsPbBr 3 The preparation method of TCPP comprises the following steps: Hydroxylated CsPbBr 3 Preparation: 4-6g CsPbBr 3 Mix with 180-220 ml of 20% sodium hydroxide aqueous solution at a mixing temperature of 80-90 ° C for 6-10 hours, then filter, wash and dry to obtain hydroxylated CsPbBr 3 ; Cb 3 -TCPP preparation: First, 7-9 g 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) was dissolved in 100 ml dimethyl sulfoxide (DMSO), and then 3.5-4.5 g hydroxylated CsPbBr was added. 3 Then, 0.1-0.2 ml of concentrated sulfuric acid was added dropwise, and the reaction was continued at 60-80 ° C for 36-50 hours. Finally, it was filtered, washed, and freeze-dried to obtain CsPbBr 3 -TCPP.
[0015] In the above preparation method, 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin is connected to CsPbBr by esterification reaction of hydroxyl and carboxyl groups. 3 This promotes the normal construction of the organic metal framework in the later stage, and the preparation method is simple and convenient to operate, and is suitable for mass production.
[0016] Preferably, the CsPbBr 3 It is obtained by covalently linking 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) via an amide bond.
[0017] Preferably, the CsPbBr 3 The preparation method of TCPP comprises the following steps: Amination of CsPbBr 3 Preparation: 4-6g CsPbBr 3 Mix with 180-220 ml of 20% ammonia water at 80-90 °C for 6-10 h, then filter and wash with dilute hydrochloric acid until neutral, and dry to obtain the aminated CsPbBr 3 ; Cb 3Preparation of TCPP: First, 70-90 mg of 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) was dissolved in 100 ml of dimethyl sulfoxide (DMSO), followed by the addition of 70-90 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and 70-90 ml of deionized water, and ultrasonic dispersion was performed for 12-18 min, followed by the addition of 150-170 mg of 1-hydroxy-2,5-pyrrolidinedione (NHS) and ultrasonic dispersion for 4-6 min, followed by the addition of 35-45 mg of amino CsPbBr 3 , stirred at room temperature for 36-50h, and finally filtered, washed, and freeze-dried to obtain CsPbBr 3 -TCPP.
[0018] Since the photodegradation of polylactic acid is essentially the degradation of ester groups, and the esterification reaction of hydroxyl groups and carboxyl groups also produces ester groups, in the subsequent photodegradation process, ultraviolet rays will first decompose the ester groups in the photon absorption promoter, and then decompose the ester groups of polylactic acid.
[0019] In the above preparation method, 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin is covalently linked to CsPbBr via an amide bond between the amino group and the carboxyl group. 3 In particular, while promoting the normal construction of the later organic metal framework, it also avoids the generation of new ester groups, allowing ultraviolet rays to act on the ester groups of polylactic acid as much as possible, thereby obtaining better photodegradation performance.
[0020] Preferably, the CsPbBr 3 The preparation method of TCPP comprises the following steps: Amination of CsPbBr 3 Preparation: 4-6g CsPbBr 3 It is mixed with 180-220 ml of 20% sodium hydroxide aqueous solution at a mixing temperature of 80-90 ° C for 6-10 hours, then filtered, washed and dried, and then added to 200 ml of ethanol and stirred evenly, and then 2-4 ml of γ-aminopropyltriethoxysilane is slowly added dropwise at 80-90 ° C, condensed and refluxed for 3-5 hours, and finally filtered, washed and dried to obtain amino CsPbBr 3 ; Cb 3Preparation of TCPP: First, 70-90 mg of 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) was dissolved in 100 ml of dimethyl sulfoxide (DMSO), followed by the addition of 70-90 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and 70-90 ml of deionized water, and ultrasonic dispersion was performed for 12-18 min, followed by the addition of 150-170 mg of 1-hydroxy-2,5-pyrrolidinedione (NHS) and ultrasonic dispersion for 4-6 min, followed by the addition of 35-45 mg of amino CsPbBr 3 , stirred at room temperature for 36-50h, and finally filtered, washed, and freeze-dried to obtain CsPbBr 3 -TCPP.
[0021] Although it is also possible to soak CsPbBr in ammonia water, 3 There are amino groups attached to the polylactic acid, but the number of amino groups attached by ammonia water is very small and the connection effect is very poor. When the metal organic framework is subsequently constructed, the amino groups are likely to be detached, thereby affecting the photodegradation effect of the final polylactic acid composition.
[0022] The above preparation method attaches the amino group to CsPbBr by means of a silane coupling agent. 3 Compared with ammonia immersion, this form of amino attachment is more stable. At the same time, the use of silane coupling agent can also promote better compatibility between the photon absorption promoter and the polylactic acid matrix, which means that the final polylactic acid composition will have a better photodegradation effect.
[0023] Preferably, the porphyrin derivative modified perovskite CsPbBr 3 The preparation method is: 8-12mgCsPbBr 3 -TCPP is dispersed in 4-6 ml N,N-dimethylformamide (DMF) and ultrasonically treated for 20-40 min, then 35-40 mg copper nitrate trihydrate and 0.1-0.2 g polyvinyl pyrrolidone (PVP) are added to 30-50 ml N,N-dimethylformamide (DMF)-ethanol mixed solution, and the mass ratio of N,N-dimethylformamide (DMF) to ethanol is 1:1; Then add CsPbBr 3 -TCPP dispersion and 40-50mg5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP), add 10-20mg trifluoroacetic acid (TFA), ultrasonically treat for 10-20min, then heat at 70-90℃ for 3-5h, and finally cool, wash, filter and dry to obtain porphyrin derivative modified perovskite CsPbBr 3 .
[0024] In a second aspect, the present application provides a method for preparing a triggerable degradable polylactic acid composition, using the following technical solution: A method for preparing a triggerable degradable polylactic acid composition comprises the following steps: Step 1, heating the polylactic acid to 160-190° C. to melt it, thereby obtaining a polylactic acid composition base material; Step 2: Cool the polylactic acid composition base material to 140-160°C, then add a photon absorption promoter, mix evenly, and extrude and form it through a screw extruder. The screw extruder has the following conditions: the first melting section temperature is 145-152°C, the second melting section is 153-159°C, the third melting section is 132-139°C, the screw speed is 60-100rpm, and the extrusion port temperature is 118-122°C.
[0025] In summary, this application has the following beneficial effects: 1. The slow photodegradation rate of polylactic acid is mainly due to its poor photon absorption performance, while the perovskite CsPbBr 3 It has excellent multi-photon absorption performance. Therefore, when polylactic acid is added with perovskite CsPbBr 3 When the perovskite CsPbBr 3 Under the action of , the photodegradation performance of polylactic acid will be significantly improved.
[0026] 2. Porphyrin has strong nonlinear optical absorption properties. Connecting metal atoms in the middle of porphyrin can further improve the properties of porphyrin. Porphyrin is constructed into a metal organic framework MOF and coated on the perovskite CsPbBr 3 After that, the perovskite CsPbBr as an inorganic component 3 It will be coordinated with the metal organic framework MOF as an organic component to promote the perovskite CsPbBr 3 The stability of the luminescent molecules and the nonlinear optical capabilities will be significantly improved, thereby obtaining a better multi-photon absorption effect.
[0027] 3. In the present application, 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin is covalently linked to CsPbBr via an amide bond between the amino group and the carboxyl group. 3 In addition, the use of silane coupling agent can promote the normal construction of the organic metal framework in the later stage, avoid the generation of new ester groups, and promote the ultraviolet rays to act on the ester groups of polylactic acid as much as possible. At the same time, the use of silane coupling agent can also promote the compatibility between the photon absorption promoter and the polylactic acid matrix to be better, which means that the final polylactic acid composition will have a better photodegradation effect. DETAILED DESCRIPTION
[0028] The present application is further described in detail below in conjunction with Examples 1-5 and Comparative Examples 1-2.
[0029] raw material Polylactic acid Total L30 from Thailand; Perovskite CsPbBr 3 Xi'an Qiyue; 5,10,15,20-Tetrakis(4-carboxyphenyl)porphyrin (TCPP) CAS: 14609-54-2; Sodium hydroxide CAS: 1310-73-2; Dimethyl sulfoxide (DMSO) CAS: 67-68-5; Concentrated sulfuric acid CAS: 7664-93-9; Ammonia CAS: 1336-21-6; Hydrochloric acid CAS: 7647-01-0; 1-Ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) CAS: 25952-53-8; 1-Hydroxy-2,5-pyrrolidinedione (NHS) CAS: 6066-82-6; γ-Aminopropyltriethoxysilane CAS: 54761-04-5; N,N-Dimethylformamide (DMF) CAS: 68-12-2; Copper nitrate trihydrate CAS: 10031-43-3; Polyvinylpyrrolidone (PVP) CAS: 9003-39-8; Ethanol CAS: 64-17-5; Trifluoroacetic acid (TFA) CAS: 76-05-1.
[0030] Example 1 A triggerable degradable polylactic acid composition is obtained by mixing polylactic acid and a photon absorption promoter, wherein the mass ratio of the polylactic acid to the photon absorption promoter is 90:10.
[0031] The preparation method of a triggerable degradable polylactic acid composition comprises the following steps: Step 1, heating the polylactic acid to 180° C. to melt it, thereby obtaining a polylactic acid composition base material; Step 2: Cool the polylactic acid composition base material to 150°C, then add the photon absorption promoter, mix evenly, and extrude and form it through a screw extruder. The screw extruder has the following conditions: the first melting section temperature is 148°C, the second melting section temperature is 155°C, the third melting section temperature is 136°C, the screw speed is 80rpm, and the extrusion port temperature is 120°C.
[0032] Photon absorption enhancer is perovskite CsPbBr modified by porphyrin derivatives 3 .
[0033] Perovskite CsPbBr modified by porphyrin derivatives 3 The preparation method comprises the following steps: Hydroxylated CsPbBr 3 Preparation: 5g CsPbBr 3It was mixed with 200 ml of 20% sodium hydroxide aqueous solution at a mixing temperature of 85 °C for 8 h, and then filtered, washed, and dried to obtain hydroxylated CsPbBr 3 ; Cb 3 -TCPP preparation: First, 8 g of 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) was dissolved in 100 ml of dimethyl sulfoxide (DMSO), and then 4 g of hydroxylated CsPbBr was added. 3 Then, 0.15 ml of concentrated sulfuric acid was added dropwise and the reaction was continued at 70 °C for 48 h. Finally, it was filtered, washed, and freeze-dried to obtain CsPbBr 3 -TCPP; Perovskite CsPbBr modified by porphyrin derivatives 3 preparation: 10mgCsPbBr 3 -TCPP was dispersed in 5 ml of N,N-dimethylformamide (DMF) and ultrasonically treated for 30 min, then 38 mg of copper nitrate trihydrate and 0.15 g of polyvinyl pyrrolidone (PVP) were added to 40 ml of N,N-dimethylformamide (DMF)-ethanol mixed solution, and the mass ratio of N,N-dimethylformamide (DMF) to ethanol was 1:1; Then add CsPbBr 3 -TCPP dispersion and 45 mg 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP), and 15 mg trifluoroacetic acid (TFA) were added, and ultrasonic treatment was performed for 15 min, and then heated at 80 ° C for 4 h, and finally cooled, washed, filtered and dried to obtain the porphyrin derivative modified perovskite CsPbBr 3 .
[0034] Example 2 The difference from Example 1 is that the perovskite CsPbBr modified by porphyrin derivatives 3 The preparation methods are different, and the specific steps are as follows: Amination of CsPbBr 3 Preparation: 5g CsPbBr 3 It was mixed with 200 ml of 20% ammonia water at 85 °C for 8 h, then filtered and washed with 10% dilute hydrochloric acid until neutral, and dried to obtain the amino CsPbBr 3 ; Cb 3Preparation of TCPP: First, 80 mg of 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) was dissolved in 100 ml of dimethyl sulfoxide (DMSO), followed by the addition of 80 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and 80 ml of deionized water, and ultrasonic dispersion for 16 min, followed by the addition of 160 mg of 1-hydroxy-2,5-pyrrolidinedione (NHS) and ultrasonic dispersion for 5 min, followed by the addition of 40 mg of amino CsPbBr 3 , stirred at room temperature for 48 h, and finally filtered, washed, and freeze-dried to obtain CsPbBr 3 -TCPP; Perovskite CsPbBr modified by porphyrin derivatives 3 preparation: 10mgCsPbBr 3 -TCPP was dispersed in 5 ml of N,N-dimethylformamide (DMF) and ultrasonically treated for 30 min, then 38 mg of copper nitrate trihydrate and 0.15 g of polyvinyl pyrrolidone (PVP) were added to 40 ml of N,N-dimethylformamide (DMF)-ethanol mixed solution, and the mass ratio of N,N-dimethylformamide (DMF) to ethanol was 1:1; Then add CsPbBr 3 -TCPP dispersion and 45 mg 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP), and 15 mg trifluoroacetic acid (TFA) were added, and ultrasonic treatment was performed for 15 min, and then heated at 80 ° C for 4 h, and finally cooled, washed, filtered and dried to obtain the porphyrin derivative modified perovskite CsPbBr 3 .
[0035] Example 3 The difference from Example 2 is that the perovskite CsPbBr modified by porphyrin derivatives 3 The preparation methods are different, and the specific steps are as follows: Amination of CsPbBr 3 Preparation: 5g CsPbBr 3 It was mixed with 200 ml of 20% sodium hydroxide aqueous solution at a mixing temperature of 85 ° C for 8 h, then filtered, washed and dried, and then added to 200 ml of ethanol and stirred evenly. Then 3 ml of γ-aminopropyltriethoxysilane was slowly added dropwise at 85 ° C, condensed and refluxed for 4 h, and finally filtered, washed and dried to obtain amino CsPbBr 3 ; Cb 3Preparation of TCPP: First, 80 mg of 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) was dissolved in 100 ml of dimethyl sulfoxide (DMSO), followed by the addition of 80 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and 80 ml of deionized water, and ultrasonic dispersion for 16 min, followed by the addition of 160 mg of 1-hydroxy-2,5-pyrrolidinedione (NHS) and ultrasonic dispersion for 5 min, followed by the addition of 40 mg of amino CsPbBr 3 , stirred at room temperature for 48 h, and finally filtered, washed, and freeze-dried to obtain CsPbBr 3 -TCPP; Perovskite CsPbBr modified by porphyrin derivatives 3 preparation: 10mgCsPbBr 3 -TCPP was dispersed in 5 ml of N,N-dimethylformamide (DMF) and ultrasonically treated for 30 min, then 38 mg of copper nitrate trihydrate and 0.15 g of polyvinyl pyrrolidone (PVP) were added to 40 ml of N,N-dimethylformamide (DMF)-ethanol mixed solution, and the mass ratio of N,N-dimethylformamide (DMF) to ethanol was 1:1; Then add CsPbBr 3 -TCPP dispersion and 45 mg 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP), and 15 mg trifluoroacetic acid (TFA) were added, and ultrasonic treatment was performed for 15 min, and then heated at 80 ° C for 4 h, and finally cooled, washed, filtered and dried to obtain the porphyrin derivative modified perovskite CsPbBr 3 .
[0036] Embodiment 4-5 The difference from Example 3 is that the mass ratio of polylactic acid to the photon absorption enhancer is different, as shown in Table 1.
[0037] Table 1 The mass ratio of polylactic acid to photon absorption promoter in Examples 3-5 Example 3 Example 4 Example 5 Polylactic acid 90 95 85 Photon absorption enhancer 10 5 15 Comparative Example 1 The difference from Example 1 is that no photon absorption enhancer is added.
[0038] Comparative Example 2 The difference from Example 1 is that the photon absorption promoter is only the perovskite CsPbBr 3 .
[0039] Performance testing Photodegradation effect test Three samples were taken from Examples 1-5 and Comparative Examples 1-2, respectively, and then each sample was made into a sample of a specified size according to the fluorescent ultraviolet lamp exposure test method of GB / T 14522-2008 "Artificial weathering test method for plastics, coatings, and rubber materials for mechanical industrial products - fluorescent ultraviolet lamp", and the irradiation intensity was 0.68W / m2×nm, the continuous illumination was 120h, the blackboard temperature was 63°C, and the tensile strength of the sample before and after aging was tested and recorded without spraying, and finally the photodegradation value was calculated; Photodegradation value = (original tensile strength - tensile strength after photodegradation) / original tensile strength × 100%.
[0040] The test data are shown in Table 2.
[0041] Table 2 Test data table of Examples 1-5 and Comparative Examples 1-2 Photodegradation value / % Photodegradation value / % Example 1 59.7% Example 5 68.0% Example 2 62.1% Comparative Example 1 36.9% Example 3 66.5% Comparative Example 2 47.4% Example 4 56.6% Referring to Comparative Examples 1 and 2 and combined with Table 2, it can be seen that the photodegradation value of Comparative Example 2 is significantly improved compared with Comparative Example 1, which shows that the perovskite CsPbBr 3 The addition of can significantly improve the photodegradation performance of polylactic acid.
[0042] The reason is that the slow photodegradation rate of polylactic acid is mainly due to its poor photon absorption performance, while the perovskite CsPbBr 3 It has excellent multi-photon absorption performance. Therefore, when polylactic acid is added with perovskite CsPbBr 3 When the perovskite CsPbBr 3 Under the action of , the photodegradation performance of polylactic acid will be significantly improved.
[0043] Referring to Example 1 and Comparative Example 2 and combined with Table 2, it can be seen that the photodegradation value of Example 1 is further improved compared with Comparative Example 2, which shows that the photodegradation value of the perovskite CsPbBr 3 Modification with porphyrin derivatives can further improve the photodegradation performance of polylactic acid.
[0044] The reason is that the perovskite CsPbBr 3 There is a certain aggregation quenching effect, which leads to relatively poor stability of the absorbed photons, that is, the perovskite CsPbBr 3 The degradation performance of polylactic acid still needs to be improved.
[0045] The structure of porphyrin is composed of four pyrrol subunits connected by four methyl bridges. The existence of the extended π-electron system in porphyrin provides the basis for various nonlinear optical effects, that is, it has strong nonlinear optical absorption properties. Connecting metal atoms in the middle position of porphyrin can further enhance the properties of porphyrin.
[0046] Metal-organic framework (MOF) is a porous ordered microporous crystalline material with a wide wavelength range and considerable nonlinear optical properties. Porphyrin is constructed into a metal-organic framework (MOF) and coated on the perovskite CsPbBr 3 After that, the perovskite CsPbBr as an inorganic component 3 It will be coordinated with the metal organic framework MOF as an organic component to promote the perovskite CsPbBr 3 The stability of the luminescent molecules and the nonlinear optical capabilities will be significantly improved, thereby obtaining a better multi-photon absorption effect.
[0047] Referring to Example 1 and Example 2 and combining with Table 2, it can be seen that the photodegradation value of Example 2 is relatively higher than that of Example 1, which shows that compared with CsPbBr 3 CsPbBr was connected with 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) by esterification reaction. 3 The polylactic acid composition can have a better photodegradation effect by connecting with 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) through an amide bond.
[0048] The reason is that in Example 1, 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin is connected to CsPbBr by esterification reaction between hydroxyl and carboxyl groups. 3 Although the preparation method is simple and convenient to operate and suitable for mass production, the photodegradation of polylactic acid is essentially the degradation of ester groups, and the esterification reaction of hydroxyl and carboxyl groups also produces ester groups. In the subsequent photodegradation process, ultraviolet rays will first decompose the ester groups in the photon absorption promoter, and then decompose the ester groups of polylactic acid.
[0049] In the preparation method of Example 2, 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin is covalently linked to CsPbBr by an amide bond between the amino group and the carboxyl group. 3 In particular, while promoting the normal construction of the later organic metal framework, it also avoids the generation of new ester groups, allowing ultraviolet rays to act on the ester groups of polylactic acid as much as possible, thereby obtaining better photodegradation performance.
[0050] Referring to Example 2 and Example 3 and in combination with Table 2, it can be seen that the photodegradation value of Example 3 is significantly improved compared with that of Example 2, which indicates that, compared with amino group attachment through ammonia water, amino group attachment through γ-aminopropyltriethoxysilane can promote the polylactic acid composition to have a better photodegradation effect.
[0051] The reason is that although CsPbBr 3 There are amino groups attached to the polylactic acid, but the number of amino groups attached by ammonia water is very small and the connection effect is very poor. When the metal organic framework is subsequently constructed, the amino groups are likely to be detached, thereby affecting the photodegradation effect of the final polylactic acid composition.
[0052] In the preparation method of Example 3, amino groups are attached to CsPbBr by means of a silane coupling agent. 3 Compared with ammonia immersion, this form of amino attachment is more stable. At the same time, the use of silane coupling agent can also promote better compatibility between the photon absorption promoter and the polylactic acid matrix, which means that the final polylactic acid composition will have a better photodegradation effect.
[0053] Referring to Examples 3-5 and in combination with Table 2, it can be seen that, relative to Example 3, the photodegradation value of Example 4 is significantly reduced, while the photodegradation value of Example 5 is slightly improved. Therefore, considering the comprehensive photodegradation effect and cost, the mass ratio of polylactic acid and the photon absorption promoter using Example 3 is relatively better.
[0054] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A triggerable degradable polylactic acid composition, characterized in that: The invention is obtained by mixing polylactic acid and a photon absorption promoter, wherein the photon absorption promoter is a perovskite CsPbBr3 modified by a porphyrin derivative.
2. The triggerable degradable polylactic acid composition according to claim 1, characterized in that: The mass ratio of the polylactic acid to the photon absorption enhancer is (85-95):(5-15).
3. The triggerable degradable polylactic acid composition according to claim 1, characterized in that: The preparation method of the porphyrin derivative modified perovskite CsPbBr3 is as follows: firstly, CsPbBr3 is connected with 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) to obtain CsPbBr3-TCPP; then, the porphyrin molecules on the CsPbBr3-TCPP are used as active growth sites to directly grow a porphyrin-based metal framework, and finally the porphyrin derivative modified perovskite CsPbBr3 is obtained.
4. The triggerable degradable polylactic acid composition according to claim 3, characterized in that: The CsPbBr3 is connected with 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) through an esterification reaction; The preparation method of the CsPbBr3-TCPP comprises the following steps: Preparation of hydroxylated CsPbBr3: 4-6g CsPbBr3 is mixed with 180-220ml of 20% sodium hydroxide aqueous solution at a mixing temperature of 80-90°C for 6-10h, followed by filtration, washing, and drying to obtain hydroxylated CsPbBr3; Preparation of CsPbBr3-TCPP: First, dissolve 7-9g 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) in 100ml dimethyl sulfoxide (DMSO), then add 3.5-4.5g hydroxylated CsPbBr3, then drop 0.1-0.2ml concentrated sulfuric acid, and continue the reaction at 60-80°C for 36-50h. Finally, filter, wash, and freeze-dry to obtain CsPbBr3-TCPP.
5. The triggerable degradable polylactic acid composition according to claim 3, characterized in that: The CsPbBr3 is covalently linked to 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) via an amide bond.
6. The triggerable degradable polylactic acid composition according to claim 5, characterized in that: The preparation method of the CsPbBr3-TCPP comprises the following steps: Preparation of amination CsPbBr3: Mix 4-6g CsPbBr3 with 180-220ml of 20% ammonia water at a mixing temperature of 80-90°C for 6-10h, then filter and wash with dilute hydrochloric acid until neutral, and dry to obtain amination CsPbBr3; Preparation of CsPbBr3-TCPP: First, dissolve 70-90 mg 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) in 100 ml dimethyl sulfoxide (DMSO), then add 70-90 mg 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and 70-90 ml deionized water, and ultrasonically disperse for 12-18 min. Then, add 150-170 mg 1-hydroxy-2,5-pyrrolidinedione (NHS) and ultrasonically disperse for 4-6 min. Then, add 35-45 mg amino CsPbBr3, stir at room temperature for 36-50 h, and finally filter, wash, and freeze-dry to obtain CsPbBr3-TCPP.
7. The triggerable degradable polylactic acid composition according to claim 5, characterized in that: The preparation method of the CsPbBr3-TCPP comprises the following steps: Preparation of amination CsPbBr3: 4-6g CsPbBr3 is mixed with 180-220ml of 20% sodium hydroxide aqueous solution at a mixing temperature of 80-90°C for 6-10h, followed by filtration, washing and drying, and then added to 200ml of ethanol and stirred evenly, followed by slow dropwise addition of 2-4ml of γ-aminopropyltriethoxysilane at 80-90°C, condensation reflux reaction for 3-5h, and finally filtration, washing and drying to obtain amination CsPbBr3; Preparation of CsPbBr3-TCPP: First, dissolve 70-90 mg 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) in 100 ml dimethyl sulfoxide (DMSO), then add 70-90 mg 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and 70-90 ml deionized water, and ultrasonically disperse for 12-18 min. Then, add 150-170 mg 1-hydroxy-2,5-pyrrolidinedione (NHS) and ultrasonically disperse for 4-6 min. Then, add 35-45 mg amino CsPbBr3, stir at room temperature for 36-50 h, and finally filter, wash, and freeze-dry to obtain CsPbBr3-TCPP.
8. The triggerable degradable polylactic acid composition according to claim 1, characterized in that: The preparation method of the porphyrin derivative modified perovskite CsPbBr3 is: 8-12 mg CsPbBr3-TCPP was dispersed in 4-6 ml N, N-dimethylformamide (DMF) and ultrasonicated for 20-40 min. Then, 35-40 mg copper nitrate trihydrate and 0.1-0.2 g polyvinyl pyrrolidone (PVP) were added to 30-50 ml N, N-dimethylformamide (DMF)-ethanol mixed solution. The mass ratio of N, N-dimethylformamide (DMF) to ethanol was 1:
1. Then add CsPbBr3-TCPP dispersion and 40-50 mg 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP), and add 10-20 mg trifluoroacetic acid (TFA), ultrasonically treat for 10-20 minutes, and then heat at 70-90°C for 3-5 hours, and finally cool, wash, filter and dry to obtain the porphyrin derivative modified perovskite CsPbBr3.
9. A method for preparing the triggerable degradable polylactic acid composition according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1, heating the polylactic acid to 160-190° C. to melt it, thereby obtaining a polylactic acid composition base material; Step 2: Cool the polylactic acid composition base material to 140-160°C, then add a photon absorption promoter, mix evenly, and extrude and form it through a screw extruder. The screw extruder has the following conditions: the first melting section temperature is 145-152°C, the second melting section is 153-159°C, the third melting section is 132-139°C, the screw speed is 60-100rpm, and the extrusion port temperature is 118-122°C.
Citation Information
Patent Citations
Preparation method of polyactic acid / polyethylene glycol biological hybrid material for PDT (photodynamic therapy)
CN103204997A
Preparation method of metal halide perovskite quantum dots
CN107603614A
Method for synthesizing CsPbBr3 perovskite stable in aqueous solution in one step
CN109762554A
Water-resistant heat-resistant perovskite nanocrystal and preparation method and application thereof
CN110643360A
Preparation method and application of high-stability perovskite luminescent material with laminated structure
CN115321586A
